OLEH-OLEH MAKANAN KHAS DAERAH ISTIMEWA YOGYAKARTA SEBAGAI DAYA TARIK WISATA GASTRONOMI - Kusumawati, Pipin; Tyas, Dyah Wahyuning; Fitriana, Fitriana; Kusumaningrum, Haritsah (Pringgitan, 2023)
Visiting a tourist destination frequently inspired the tourist to purchase the food souvenirs for one's family or close acquaintances. They desired to bestow upon those closest to them a memento or impression of a tourist destination in addition to an expression of affection. Yogyakarta Special Region (DIY) is a popular tourist destination among both domestic and international visitors. Recognizing this opportunity, numerous small and medium-sized enterprises (SMSE) manufactured the assortment of foods intended for sale to tourists as food gifts. Many of these options, however, were "contemporary", in accordance with the preferences of the youth market, so they were not entirely "authenthic" of Jogja. This may cause confusion among tourists seeking the typical DIY food souvenirs. Thus, there was a need for explanation to various types of authentic DIY food souvenirs that were historic, authentic from each district in DIY and have survived for more than two generations, representing the DIY's identity. The authentic food souvenirs can also act as a gastronomic tourist attraction in a tourist destination.Keywords: Souvenirs; Food; Authentic; Gastronomy